Growth and Morphology Modulation of Needle-like Silicon Nanowires for SERS Application. Issue 11 (November 2015) - Jian, Huang; Dayan, Ma; Kewei, Xu
Abstract: Semiconductor nanowires are attracting intense interest as a promising substrate material for surface enhanced Raman spectroscopy (SERS). Based on vapor-liquid-solid (VLS) procedure using Au as a catalyst, silicon nanowires (SiNWs) with controllable diameters were developed by the plasma enhanced chemical vapor deposition (PECVD) system. Inspired by the fact that the morphology of SiNWs can be effectively modulated by tuning the size of catalyst droplets, we designed a needle-like SiNWs owing to the shrink and consumption of Si-Au catalyst droplets. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) analyses reveal that crystalline Si phase is possessed of amorphous SiO2 in the as-prepared coaxial nanowires. The morphology of the prepared SiNWs was examined by scanning electron microscope (SEM). As SERS active substrates, Ag nanoparticles were synthesized on surface of SiNWs by galvanic displacement. Results show that enhancement factor (EF) of SERS achieved on the prepared needle-like SiNWs/Ag is more than 10 times than that of cylindrical-shaped SiNWs/Ag for R6G molecules detection. It is supposed that needle-like SiNWs composited with Ag nanoparticles can be exploited as a new type nanosensor, environmental monitoring or biomedical diagnostics. In addition, many other needle-like semiconductor nanowires such as germanium needle-like nanowires also can be prepared by similar method in the present study.